Advanced Initiatives in Interprofessional Education in Japan Japan Interprofessional Working and Education Network - Watanabe, Hideomi; Koizumi, Misako; SpringerLink (Online service) (Tokyo : Springer Japan, 2010)
Interprofessional education (IPE) is becoming a recognized discipline among health care professionals and medical training institutions worldwide. Its significance is especially felt in Japan, where little has been written on the subject although the need is great. Recent initiatives among several institutions have helped to create the Japan Interprofessional Working and Education Network (JIPWEN), comprising ten universities. Through consultation and cooperation with the World Health Organization, other international networks, and local health policy planners, JIPWEN focuses on critical issues and applicable models to assist institutions interested in setting up IPE programs. With contributions from the ten JIPWEN member universities, this book explains in detail the diverse contents of existing IPE programs and provides viable models for the increasing number of institutions aiming to develop their own IPE programs. The chapters that make up the book depict the member institutions' backgrounds, goals, methods, modules, student compositions, facilitation systems, and curricula, providing an invaluable description of IPE initiatives currently under way in Japan.
Encouraging Appreciation of Community Health Care by Consistent Medical Undergraduate Education -- Interprofessional Education at Niigata University of Health and Welfare -- Interprofessional Education Program of the University of Tsukuba: A Program to Develop Interprofessional Competence -- Community-Based Interprofessional Education at Saitama Prefectural University -- Jikei University School of Medicine: An Interprofessional Medical Education Program -- Interprofessional Education at the Keio University Faculty of Pharmacy -- Support Program for Contemporary Educational Needs: (3z(BContemporary Good Practice(3y (BProject at Chiba University -- Interprofessional Team-Based Medical Education Program at Kitasato University: Collaboration Among 14 Health-Related Professions -- Becoming Interprofessional at Kobe University -- Interprofessional Education Initiatives at Gunma University: Simulated Interprofessional Training for Students of Various Health Science Professions.s
Keywords: Medicine; Physical therapy; Medicine & Public Health; Physiotherapy